Taxifolin acts as type I inhibitor for VEGFR-2 kinase: Stability evaluation by molecular dynamic simulation - Sharad Verma, Amit Singh, Abha Mishra (Journal of Applied Pharmaceutical Science)
The VEGFR-2 kinase specific intracellular signalling cascades leading to proliferation, migration, survival of endothelial cells and increased permeability of vessels which contributes to angiogenesis. ATP is essentially required by VEGFR-2 to perform phosphorylation of specific proteins and to maintain cascade downstream. Taxifolin (plant polyphenol) inhibit the VEGFR-2 kinase by binding at ATP-binding pocket revealed by molecular docking study. Further, stability of VEGFR-2 kinase-taxifolin complex is validated by molecular dynamic simulation. RMSD analysis for 3800 ps confirmed the stability of complex. Furthermore, thermodynamic stability was evidenced by stable total energy, potential energy, and, temperature and pressure profile. After MD simulation taxifolin was found to stably interact with pocket residues Cys 917 and Lys 1053 along with water molecules. These results suggest that therapeutic inhibition of VEGFR-2 by taxifolin as a type I inhibitor may be a promising ways to retard signaling cascade of specific proteins which play crucial role in cancer proliferation and also in development of second generation type II inhibitors.
Keywords: VEGFR-2, taxifolin, molecular dynamic simulation, type I inhibitor, DFG-out